1988
DOI: 10.1042/bj2520553
|View full text |Cite
|
Sign up to set email alerts
|

Binding of rat chylomicrons and their remnants to the hepatic low-density-lipoprotein receptor and its role in remnant removal

Abstract: Binding and uptake of rat chylomicrons of different metabolic stages by the hepatic low-density-lipoprotein (LDL) receptor were studied. Pure chylomicrons, characterized by apolipoprotein B-48 devoid of contaminating B-100, were labelled in their cholesteryl esters. Lymph chylomicrons and serum chylomicrons, enriched in apolipoprotein E and the C-apolipoproteins, bound poorly to rat hepatic membranes. In contrast, chylomicron remnants, containing the apolipoproteins B-48 and E, bound with high affinity. Specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
32
0
3

Year Published

1990
1990
2005
2005

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 39 publications
3
32
0
3
Order By: Relevance
“…On the other hand, chylomicron remnants have been demonstrated to bind to the LDLR through apoE that forms a major surface component of the lipoproteins in in vitro studies (15,(17)(18)(19). When the LDLR was blocked by its monospecific antibody in mice (20) and rats (21), the clearance of chylomicron remnants was partially delayed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, chylomicron remnants have been demonstrated to bind to the LDLR through apoE that forms a major surface component of the lipoproteins in in vitro studies (15,(17)(18)(19). When the LDLR was blocked by its monospecific antibody in mice (20) and rats (21), the clearance of chylomicron remnants was partially delayed.…”
mentioning
confidence: 99%
“…In support of this, the intravenously injected chylomicrons was cleared from the plasma of LDLR-deficient rabbits at a rate similar to wild-type (15). Upon vitamin A fat tolerance tests, moreover, no significant delay of the excursion of the esterified form of vitamin A, which represents chylomicron remnants, was shown in LDLR-deficient humans (16).On the other hand, chylomicron remnants have been demonstrated to bind to the LDLR through apoE that forms a major surface component of the lipoproteins in in vitro studies (15,(17)(18)(19). When the LDLR was blocked by its monospecific antibody in mice (20) and rats (21), the clearance of chylomicron remnants was partially delayed.…”
mentioning
confidence: 99%
“…Previous experiments (2-6, 10) showed that the uptake of CRs is mediated by apolipoprotein E (apoE) but is independent of apoB (11). Since the low density lipoprotein (LDL) receptor is able to recognize apoE with high affinity, one line of thinking assumed that the LDL receptor was responsible for CR catabolism (12), and this appears to be true in part. However, tissue culture studies as well as in vivo experiments have shown that most of the apoE-mediated uptake of CR is independent of the LDL receptor (13,14).…”
mentioning
confidence: 99%
“…Hepatic LDL receptors were reported to be situated at the basolateral surface of hepatocytes (23). The similar pattern of apoE and LDL receptors suggests that enrichment of chylomicrons and remnants with apoE may be immediately followed by hepatic uptake through LDL receptors, since several lines ofevidence indicate that LDL receptors play a major role in plasma clearance ofchylomicron remnants in rodents (21,22,24). LRP, which is as likely a candidate as chylomicron remnant receptors, appears to be also similarly localized and involved in hepatic uptake of chylomicrons and remnants.…”
Section: Discussionmentioning
confidence: 96%
“…It is now established that hepatic overexpression of apoE markedly enhances plasma clearance of chylomicron remnants. A high apoE content on chylomicron remnants would be essential to an efficient receptor mediated-endocytosis, although functional proposition of LDL receptors and chylomicron remnant receptors that might be LRP is controversial (19)(20)(21)(22). The chylomicrons used in this study were prepared from pleural effusions of a patient with chylothorax and were relatively poor in apoE.…”
Section: Discussionmentioning
confidence: 99%